2006
DOI: 10.1093/molbev/msl081
|View full text |Cite
|
Sign up to set email alerts
|

Protein Evolution Is Faster Outside the Cell

Abstract: Some proteins are highly conserved across all species, whereas others diverge significantly even between closely related species. Attempts have been made to correlate the rate of protein evolution to amino acid composition, protein dispensability, and the number of protein-protein interactions, but in all cases, conflicting studies have shown that the theories are hard to confirm experimentally. The only correlation that is undisputed so far is that highly/broadly expressed proteins seem to evolve at a lower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
84
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 52 publications
10
84
3
Order By: Relevance
“…The analysis of the versatility of the old and young domains also showed that the young domains are the most versatile; with a versatility index twice that of other domain classes. The analysis of sub-cellular localization indicated that modern domains are mainly located in the proteins of extracellular regions and in extracellular segments of membrane proteins, consistent with previous studies showing that proteins in extracellular regions evolve faster than those of intracellular proteins (Julenius & Pedersen, 2006). Most old domains are located in the nucleus and cytoplasm.…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of the versatility of the old and young domains also showed that the young domains are the most versatile; with a versatility index twice that of other domain classes. The analysis of sub-cellular localization indicated that modern domains are mainly located in the proteins of extracellular regions and in extracellular segments of membrane proteins, consistent with previous studies showing that proteins in extracellular regions evolve faster than those of intracellular proteins (Julenius & Pedersen, 2006). Most old domains are located in the nucleus and cytoplasm.…”
Section: Discussionsupporting
confidence: 88%
“…We built a phylogeny using the naive MSA, and we built two phylogenies each from the structural unmasked and masked MSAs. Previous work has shown that combined structural and functional constraints impose differing selection pressures in TM vs. extramembrane (EM) domains, in turn producing distinct amino-acid frequency distributions in each domain class (Tourasse and Li, 2000;Stevens and Arkin, 2001;Julenius and Pedersen, 2006;Oberai et al, 2009;Spielman and Wilke, 2013;Franzosa et al, 2013). As our structurally-curated MSAs allowed us to precisely identify each MSA column as either TM or EM, we were able to conduct far more rigorous phylogentic inference using a partitioned analysis.…”
Section: Structurally-aware Msa Strongly Improves Phylogenetic Inferencementioning
confidence: 99%
“…An obvious sequence adaptation is the hydrophobic matching of the protein exterior, reflected in an apolar transmembrane amino acid composition. Although amino acid diversity is more limited in the transmembrane segments, simple compositional differences do not explain the slower divergence rates of transmembrane regions (1,4,5).…”
mentioning
confidence: 92%
“…disease mutation ͉ potassium channel ͉ protein folding ͉ protein stability ͉ single nucleotide polymorphisms E volutionary rates vary considerably in different cellular compartments (1). Membrane proteins have been found to diverge faster overall than soluble proteins (2,3), but this increased rate is confined entirely to the rapidly evolving extramembrane regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation